Early Rehabilitation Reduces Time to Decannulation in Patients With Severe Acquired Brain Injury: A Retrospective Study - Zivi, Ilaria; Valsecchi, Roberto; Maestri, Roberto; Maffia, Sara; Zarucchi, Alessio; Molatore, Katia; Vellati, Elena; Saltuari, Leopold; Frazzitta, Giuseppe (Frontiers in Neurology, 2018)
Purpose: Early decannulation is considered a main rehabilitative goal in tracheostomized patients. Our aim is to evaluate whether a very early rehabilitation protocol helps to reduce the tracheostomy duration in patients affected by an Acquired Brain Injury (ABI). Methods: Data about consecutive tracheostomized patients admitted in our Neuro-Rehabilitation Unit (NRU) were retrospectively collected. We defined two groups: Early Rehabilitation Group patients came from our ICU, where they started the rehabilitative treatment; Delayed Rehabilitation Group patients arrived from external ICUs and started rehabilitation in our NRU. Primary outcome was the time from tracheostomy to decannulation. Secondary outcomes were: ICU length of stay, time from NRU admission to decannulation, Glasgow Coma Scale, Coma Recovery Scale revised and Levels of Cognitive Functioning scores at NRU discharge and the re-cannulation rate. Results: We enrolled 66 patients, 40 in the Early Rehabilitation Group and 26 in the Delayed Rehabilitation Group. 70% of patients for each group could be decannulated (p=0.73) and were analyzed. Only one patient was re-cannulated. Early Rehabilitation Group showed a shorter tracheostomy duration (61.0 vs 94.5 days, p=0.013), a higher probability of occurrence of decannulation (p=0.008) and a lower ICU length of stay (30.0 vs 52.0 days, p=0.001). The time to decannulation in NRU was similar between groups (30.0 vs 45.50 days, p=0.14). All the scale scores had a significant improvement in both groups (p<0.0001 all). Conclusions: The present study shows that an early neuro-rehabilitation protocol helps to reduce the time to decannulation in tracheostomized patients affected by ABI.